The economic bases of migration from Italy: the distinct cases of Tunisia and Libya (1880s–1960s). Issue 3 (3rd May 2020) - Fauri, Francesca; Strangio, Donatella
ABSTRACT: The objective of this essay is to offer an original contribution to the issue of Italian migration to Africa from a historical-economic perspective. Our research will consider the motivations that led many Italians to emigrate to Tunisia and Libya and, secondly, it will explore what was the return path from Tunisia and Libya for Italian emigrants. The cases discussed investigate two different realities of Italian emigration, a 'free' migration toward a country colonised by others and a migration imposed and sponsored by the Italian-government. In the first case, we observed how Italians, particularly from the South and the islands, were predominantly drawn to Tunisia because the country was geographically close and offered good economic opportunities to Italian emigrants. In the case of Libya, the fascist colonial model aimed at creating settlements inhabited by Italians regardless of the real opportunities offered by the land to Italian migrants. The reasons behind the repatriations, in both cases, lie in the decolonisation of the African continent. The decolonisation process in both countries proceeded through a first phase where they privileged the recruitment of local or 'African' workforce rather than 'foreign/Italian' labourers, and a second phase that saw the requisition of all foreign assets and properties.